Scientific Attitude Inventory of Junior High School Students During Pandemic - Capiral, Christine Ivy S. (Future Science / FSH-PH Publications, 2022)
The study sought to analyze the scientific attitude inventory of junior high school students during pandemic. The scientific attitudes are the most important outcomes of science teaching. It is the combination of many qualities and virtues that is reflected in a person's behavior and actions. The aim of the present study is to check scientific attitude inventory among junior high school students. This study covers 350 students from the different grade levels. Subjects were selected using a stratified random sampling method. Scientific Attitude Scale (SAS) of Bajwa and Mahajan (2012) was administered to collect the data. The statistical treatments that were used in this study are Independent T-test and One way Analysis of Variance (ANOVA) to determine the significant difference assessment of respondents about scientific attitude inventory when grouped according to their profile characteristics. On the other hand, the data statistical treatments that were used to determine the significant relationship of scientific attitude and academic performance is Spearman’s Rho Correlation Coefficient. The findings of the study revealed that there is no significant difference between scientific attitude and profile characteristics of the respondents. It also revealed that there is no significant relationship between scientific attitude and academic performance of the respondents. It may therefore be concluded that the scientific attitude of students during pandemic have less in comparison to the normal.